Integrales de resonancia de activación de neutrones 74Se, 78Se, 80Se, 81Br, 127I, 130Te, 1Ba, 140Ce, 142Ce - Bovisio de Ricabarra, M.D.; Bighman, C.B.; Ricabarra, G.H.; Faradjie de Turjanski, Rosa (Comisión Nacional de Energía Atómica (CNEA), 1970)
Fil:Bovisio de Ricabarra, M.D. Comisión Nacional de Energía Atómica (CNEA). República Argentina